(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines the significance of evaluating materials and textbooks in English language teaching. It also analyzes key principles underlying the selection of instructional materials. Furthermore, it explores evaluation frameworks proposed by linguists such as Williams, Breen, McDonough and Shaw, and Grant.